Müntz spaces and special Bloch type inequalities. Issue 7 (3rd August 2018) - Lefèvre, Pascal
Abstract: In this paper, we are interested in classical Müntz spaces and their properties. We first reprove Müntz theorem and obtain the Clarkson–Erdös–Schwartz expansion in the nondense case for some general abstract Müntz spaces without invoking any blow up property, but using classical complex variables tools. We introduce new Bloch type Müntz spaces and investigate the validity of Bloch type inequalities in this framework.